Obesity, eating habits and nutritional knowledge among school children - Triches, Rozane Márcia (2005)
OBJECTIVE: To evaluate the association between obesity and eating habits and nutritional knowledge among schoolchildren. METHODS: Weight and height were measured in 573 schoolchildren of public schools in two cities of State of Rio Grande do Sul, Southern Brazil. Obesity was defined as Body Mass Index above the 95th percentile based on the National Center for Health Statistics (NCHS) criteria. Eating habits and nutrition knowledge were evaluated using a self-administered questionnaire. Simple and adjusted logistic regression models were used to assess associations. RESULTS: Obesity among children was found to be associated with limited nutrition knowledge and unhealthy eating and habits. These children were five times more likely to be obese (OR=5.3;1.1-24.9). CONCLUSIONS: The level of knowledge affects the association between obesity and eating habits, and there's reason to suspect that children who have more nutrition knowledge report habits known to be healthier but not necessarily the ones they actually practice. Taking into account children's level of knowledge, unhealthy habits were strongly associated to obesity.